2006
DOI: 10.1345/aph.1g384
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole-lnduced Thrombocytopenia

Abstract: Although drug-induced thrombocytopenia with pantoprazole appears to be rare, it represents a potentially severe adverse effect. This supports the judicious prescribing of pantoprazole and possibly other proton-pump inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 5 publications
1
20
1
Order By: Relevance
“…They are also important for the treatment of peptic ulcers, especially in acute settings when patients present with upper gastrointestinal bleeding [12]. Generally, PPIs are very safe medications, but a few case reports have implicated their role in causing thrombocytopenia [28, 33]. This side effect of PPIs should be taken seriously, as the drop in the platelet count in our patient was very severe, and this side effect poses significant consequences such as life-threatening bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also important for the treatment of peptic ulcers, especially in acute settings when patients present with upper gastrointestinal bleeding [12]. Generally, PPIs are very safe medications, but a few case reports have implicated their role in causing thrombocytopenia [28, 33]. This side effect of PPIs should be taken seriously, as the drop in the platelet count in our patient was very severe, and this side effect poses significant consequences such as life-threatening bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few case reports have shown an increased incidence of rebound gastrointestinal symptoms and community-acquired pneumonia after short-term PPI use [26, 27]. While nine case reports and one retrospective study have demonstrated that PPIs may cause thrombocytopenia, another large retrospective study failed to show any increased incidence of thrombocytopenia after PPI use [28–38]. …”
Section: Introductionmentioning
confidence: 99%
“…These agents are generally well tolerated, with few commonly reported adverse effects (1). A rarely reported adverse effect consists of thrombocytopenia associated with the use of PPIs (2)(3)(4)(5). We describe a case in which the patient developed thrombocytopenia while taking intravenous pantoprazole.…”
mentioning
confidence: 95%
“…Departments of 1 Gastroenterology, 2 Internal Medicine, 3 Surgery, 4 Radiology, 5 The To the Editor, Proton-pump inhibitors (PPIs) are prescribed for treatment of peptic ulcer disease, gastroesophageal reflux disease, acute gastrointestinal bleeding, Zollinger-Ellison syndrome, and Helicobacter pylori eradication. These agents are generally well tolerated, with few commonly reported adverse effects (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation